Empirical study of human capital management as a knowledge-based strategic asset in building sustainability of public companies in Indonesia - Istikhoroh, Siti; Suning; Ardhiani, Mutiara Rachma; Miradji, Mohammad Afrizal (International Journal of Management and Sustainability, 2025)
This study examines human capital as a strategic asset in achieving organizational sustainability within the triple bottom line (TBL) framework. It explores knowledge management as a mediating variable and relational capital as a moderating factor. A quantitative approach was employed, surveying 277 companies across 12 industrial sectors listed on the Indonesia Stock Exchange (IDX). Data were collected through structured questionnaires and analyzed using path analysis with SmartPLS software. The results indicate that human capital, knowledge management and relational capital significantly impact organizational sustainability (p ≤ 0.05). Knowledge management mediates the relationship between human capital and sustainability whereas relational capital does not significantly moderate these relationships. This study reinforces resource-based theory, demonstrating that knowledge-based assets drive competitive advantage due to their unique and inimitable nature. Relational capital’s influence on sustainability is more direct rather than moderating while knowledge management plays a crucial mediating role. The findings provide strategic insights for business leaders to optimize human capital and knowledge management for sustainability. Companies should focus on fostering a knowledge-driven culture and leveraging human capital as a core asset while maintaining strong stakeholder relationships to support long-term sustainability.